Using the CTL Learning Model assisted by Flipbook to improve student learning outcomes at SMPN 7 Surabaya - Mashudi, Mashudi (FKIP Universitas Lampung, 2023)
This classroom action research investigated the enhancement of student engagement and academic performance in a class VIII cohort at SMPN 7 Surabaya, utilizing a contextual learning model augmented with flipbook media. The study spanned two cycles and involved a group of 32 students. The first cycle's findings indicated a moderate level of student learning completion and an average achievement score of 69.44. In the subsequent cycle, there was a marked improvement in learning outcomes, with a significant rise in the average score to 80.40, reflecting the increased efficiency of the learning process. These results demonstrate that the incorporation of flipbook media into the contextual learning framework notably benefits student participation and academic success, particularly in understanding the Position and Function of Pancasila material. This approach was thus concluded to be effective in fostering better learning experiences and outcomes for the eighth-grade students at SMPN 7 Surabaya during the first semester of the academic year 2023-2024.Keywords: Contextual Learning, Flipbook, Learning outcomes,, Learning PerfectionDOI: http://dx.doi.org/10.23960/E3J/v6i2.198-206